Data for "Sr/Ca in shells of laboratory-grown bivalves (Arctica islandica) serves as a proxy for water temperature – Perspectives for (paleo)environmental research?" - Brosset, Cornélia; Höche, Nils; Witbaard, Rob; Nishida, Kozue; Shirai, Kotaro; Mertz-Kraus, Regina; Schöne, Bernd R. (Zenodo, 2023)
This repository contains all data generated for the publication "Sr/Ca in shells of laboratory-grown bivalves ( Arctica islandica ) serves as a proxy for water temperature – Perspectives for (paleo)environmental research?" currently under review.